Flexural and Impact Properties of A New Bulletproof Vest Insert Plate Design Using Kenaf Fibre Embedded With X-Ray Films. (2018) - Azmi, A.M.R.; Sultan, M.T.H.; Hamdan, A.; Nor, A.F.M.; Jayakrishna, K.
Abstract: Current bulletproof vests are effective but not optimized in terms of cost and weight. Hence, consumers desire a more user friendly, lighter and cheaper bulletproof vest. This study discusses flexural characterization and high velocity impact testing on new composite materials to replace the existing insert panel for the existing bulletproof vest. The materials chosen for this research are kenaf fibre which is a natural fibre, and used x-ray films as a mean of recycling. The materials were fabricated using the traditional hand lay-up method into seven layers of different configurations. From the flexural characteristics, the third configuration was proposed as the best configuration and subjected to high-velocity impact test.